TREN PENGGUNAAN TEKNOLOGI PEMBELAJARAN - Nasron HK; Albetrik Meizontara; Bogi Krisnajaya; Dwi Nurprasetya; Yenni Pusvita Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT This research aims to analyze learning technology trends. This research uses the literature study method. The research results are: Learning Technology is a systematic effort to design, process and assess all learning processes that have specific objectives and are based on research on learning processes and interactions that combine human resources and effective learning. The role of learning technology is: (1) Building collaborative communication networks between teachers and students, (2) Providing various complex, realistic and safe problem solving environments, (3) Building and forming meaning actively via the internet. The principles of learning technology are absolutely necessary to implement, in order to increase the progress of a nation in an increasingly modern era of development. In implementing learning technology, you can utilize information technology and network-based learning media such as Zoom, Google Meet, Google Drive, Google Form, Google Classroom and YouTube Studio. The positive impacts of using learning technology are: (1) The emergence of Mass Media, especially electronic media as a source of knowledge and a center for education, (2) The emergence of new learning methods, (3) The learning system does not have to be face-to-face, (4) The existence of assessment results data processing system that uses technology, (5) Meeting the need for educational facilities can be met quickly. Meanwhile, the negative impacts are: (1) Utilization of information technology but not optimally, (2) Can be affected by information overload, (3) Many students become addicted to cyberspace or the internet, (4) There are criminal acts (Cyber ​​Crime).